Assessment of microRNA‐144‐5p and its putative targets in inflamed gingiva from chronic periodontitis patients. (18th November 2018) - Li, Jianjia; Wang, Runting; Ge, Yihong; Chen, Danhong; Wu, Buling; Fang, Fuchun
Abstract : Background and Objective: This study aimed to discover the distinctive MicroRNAs (miRNA) functioning in the pathogenesis of periodontal inflammation, which might be potential therapy targets of chronic periodontitis. Material and Methods: miRNA profiles of human inflamed gingival tissue from three previous microarrays were re‐analysed. Gingival tissues were collected for the validation of overlapping miRNAs, and a network was constructed to show regulatory connection between overlapping miRNAs and periodontitis‐associated target genes. Potential miRNAs were screened based on their expression levels and predicted target genes. Correlation analysis and binding site prediction were conducted to reveal the relationship between the potential miRNAs and their target genes. Results: miR‐144‐5p, found to be upregulated in all three studies, showed the greatest upregulation ( P  <   0.0001). Another 16 miRNAs (10 upregulated and six downregulated) overlapped between any two of the three studies. All overlapping miRNAs had expected expression levels except for miR‐203 during validation. Ten miRNAs (six upregulated and four downregulated) were found to have periodontal inflammation‐associated targets. Cyclooxygenase 2 ( COX2 ) and interleukin‐17F ( IL17F ), predicted target genes of upregulated miR‐144‐5p, showed significant decreases and were negatively correlated with miR‐144‐5p in the periodontitis group ( r  = −0.742 for COX2, r  = −0.615 for IL17F ). Conclusion: This re‐analysis of miRNA signatures has implied the potential regulatory mechanism of miR‐144‐5p and its potential for exploring alternative therapeutic approaches, especially those that use miRNA delivery systems to treat chronic periodontitis. Nevertheless, further study based on larger sample size and homogenous cells is needed to reveal the exact roles of miRNAs in chronic periodontitis.